KEANEKARAGAMAN MAKROZOOBENTOS DI SUNGAI BAH BOLON KABUPATEN SIMALUNGUN SUMATERA UTARA - Natalia Lusianingsih Sumanto (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Simalungun City has a very wide river ecosystem. This ecosystem is surrounded by a variety of industries and is likely to dump its waste into rivers. This can have an impact on the diversity of living things in the waters. This study aims to determine the diversity of macrozoobenthos as an indicator of water quality. The purposive random sampling method was used to determine 4 sampling stations. Samples were taken 3 times with an interval of 2 weeks. Data were then analyzed using a diversity index. The results found that the phylum Annelids, Arthropods, and Mollusks are divided into 20 genera. Cyrnellus genus has the highest density value at the cigarette factory waste disposal site that is 87.40 ind / m2. The highest diversity index is found in ice plant waste disposal sites and the highest uniformity index is found in locations free of human activity. Physical chemical factors have a strong correlation with macrozoobenthos diversity.